The Role and Meaning of Time in European Migration Law - Stronks, Martijn; Mindus, Patricia; Stern, Rebecca Thorburn (European Public Law, 2025)
This special issue deals with temporalities in migration law with particular emphasis on the European context. At the crossroads of several legal fields, including public law, human rights law, EU law and public international law, the topic is cutting-edge in migration law. The articles collected were originally presented at a conference organized at Vrije Universiteit in Amsterdam in June 2023 and another organized at Uppsala University in September 2024, both dealing with time and temporalities in migration law from a variety of perspectives. The aim of these conferences was to further develop the study of the roles of time in European migration law by unpacking the diversity of ways in which time works as an instrument of migration control in Europe. While temporal governance is far from limited to the European context – the US ‘remain in Mexico’ policy7 and the Australian temporary protection visa8 being only two examples – Europe is an interesting site of analysis. It is a forerunner in creating ‘innovative’ migration control policies9; it combines opposites, such as unhindered international movement within Europe for some, e.g., European citizens, alongside fierce immobility and stuckedness for others; it is characterized by a multilevel interplay marking the complexities of interaction between a multitude of different legal regimes and jurisdictions – domestic, EU and international (including the ECHR) – with strong human rights institutions and frameworks. This combination makes Europe a privileged site of inquiry. Drawing on this ‘forerunner quality’ and characterizing elements, this Introduction poses the question whether it is possible to distinguish a form of time one could call ‘European time’ to describe a specifically European approach to implementing temporal governance techniques in the field of migration.
Keywords: European migration law; European time; human rights law; migration studies; temporal governance; temporal othering; temporality; time; time and migration; time and migration law